3. Phase 3 Pivotal Evaluation of 20-valent Pneumococcal Conjugate Vaccine (PCV20) Safety, Tolerability, and Immunologic Noninferiority in Participants 18 Years and Older. (31st December 2020) - Essink, Brandon; Sabharwal, Charu; Xu, Xia; Sundaraiyer, Vani; Peng, Yahong; Moyer, Lisa; Pride, Michael W; Scully, Ingrid L; Jansen, Kathrin U; Gruber, William C; Scott, Daniel; Watson, Wendy
Abstract: Background: PCV20 contains the 13-valent pneumococcal conjugate vaccine (PCV13) components, and 7 additional conjugates (for serotypes 8, 10A, 11A, 12F, 15B, 22F, and 33F), extending pneumococcal serotype coverage. Key data from the pivotal Phase 3 evaluation of PCV20 in adults are presented. Methods: Adults naïve to pneumococcal vaccination were enrolled into 3 age cohorts (≥60, 50–59, and 18–49 years of age). Participants ≥60 years received either PCV20 and saline 1 month later, or PCV13 and 23-valent pneumococcal polysaccharide (PPSV23) 1 month later (1:1 randomization, double blind). Participants 50–59 and 18–49 years received either a dose of PCV20 or PCV13 (3:1 randomization, double blind). Tolerability, safety and immunogenicity (opsonophagocytic activity [OPA] responses) were assessed. Results: 3889 participants received vaccine. 1507 and 1490 participants ≥60 years received PCV20 or control respectively. All 20 vaccine serotypes induced robust responses and OPA geometric mean titers (GMTs) to all 13 matched serotypes were noninferior to PCV13. In addition, the OPA GMTs to 6 of the 7 additional serotypes 1 month after PCV20 were noninferior compared to the same serotypes in PPSV23. The OPA GMT of serotype 8 missed noninferiority by a very narrow margin (2-sided 95% lower bound of GMT ratio [20vPnC/PPSV23] was 0.49, with noninferiority criterion of >0.5); this is unlikely to be clinically significant given the high geometric mean fold rise of OPA titers after PCV20 (22-fold above baseline). GMTs after PCV20 in each of the younger age cohorts (18–49 years, 50–59 years) were noninferior to adults 60–64 years. The tolerability and safety profile of PCV20 was similar to PCV13. Conclusion: Based on the robust immune responses and comparability to licensed pneumococcal vaccines, as well as bridging to the younger age group, these data support that PCV20 will be protective against pneumococcal disease due to the 20 serotypes in adults. Disclosures: Charu Sabharwal, MD, MPH, Pfizer (Employee, Shareholder) Xia Xu, PhD, Pfizer (Employee, Shareholder) Vani Sundaraiyer, PhD, MS, Pfizer (Independent Contractor) Yahong Peng, PhD, Pfizer (Employee, Shareholder) Lisa Moyer, BS, Pfizer (Employee, Shareholder) Michael W. Pride, PhD, Pfizer (Employee, Shareholder) Ingrid L. Scully, PhD, Pfizer Inc (Employee, Shareholder) Kathrin U. Jansen, PhD, Pfizer (Employee, Shareholder) William C. Gruber, MD, Pfizer (Employee, Shareholder) Daniel Scott, MD, Pfizer (Employee, Shareholder) Wendy Watson, MD, Pfizer (Employee, Shareholder)